Estimation of the Potential Carbon Emission from Acrotelmic and Catotelmic Peats - Nurzakiah, Siti; Sabiham, Supiandi; Nugroho, Budi; Nursyamsi, Dedi (JOURNAL OF TROPICAL SOILS, 2014)
Agricultural development on peatland in Indonesia has been constrained by the presence of environment issues in relation to the release of greenhouse gases (GHGs) particularly carbon dioxide (CO2) and methane (CH4) to the atmosphere. This study was aimed to predict the potential carbon emission based on carbon stocks in acrotelmic and catotelmic peats with the reference of groundwater level of peatland.  The results showed that groundwater levels have played an important  role  in  carbon  release, which  has  close  relationship  with  water  regime  of  the upper  layer  of  peats  that influenced by oxidative and reductive conditions of the land.  From the layer that having groundwater level fluctuations during the period from rainy to dry season (acrotelmic peat), the emissions were mostly dominated by CO2 release, while from permanent reductive-layer (catotelmic peat) was not detected.  The decrease of groundwater level from -49.6 to -109 cm has clearly influenced carbon emission.  From each decreasing 1.0 cm groundwater level, CO2 emission measured during the period of February - October 2013 was calculated to yield about 0.37 Mg ha-1 yr-1.Keywords: Acrotelmic and catotelmic peat, carbon emission, groundwater level [How to Cite: Siti N, S Sabiham, B Nugroho and Di Nursyamsi. 2014. Estimation of the Potential Carbon Emission from Acrotelmic and Catotelmic Peats. J Trop Soils 19(2): 91-99. Doi: 10.5400/jts.2014.19.2.91]